Implementasi Metode Story Telling Dalam Meningkatkan Kemampuan Speaking Siswa Dengan Pemanfaatan Media StoryBook Digital Berbasis Local Wisdom - Eli Nofriati; Fina Meilinar; Zuraini Zuraini; Syarifah Khuzaimah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to enhance students’ speaking skills through the implementation of the storytelling method supported by digital storybooks based on local wisdom. Students’ low speaking ability in English learning was influenced by the limited use of teaching methods and learning media that were less engaging and not contextualized with their real-life environment at SMP Negeri 1 Muara Batu. Storytelling was chosen as it promotes an active, communicative, and meaningful learning atmosphere, while digital storybooks incorporating local wisdom were used to increase students’ motivation and participation. The study employed qualitative and quantitative approaches using a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 30 students of class VIII Merdeka 1. Data were collected through speaking tests, observation sheets of students’ and teacher’s activities, and documentation. Speaking performance was assessed based on pronunciation, fluency, vocabulary, and meaning comprehension. The findings revealed a significant improvement in students’ speaking skills, with the average score increasing from 50.5 in Cycle I to 80.2 in Cycle II. Students’ learning activities and participation also improved from 60% to 78%. In addition, the teacher’s performance in implementing the storytelling method increased from 65% in Cycle I to 85% in Cycle II. These results indicate that storytelling supported by digital storybooks based on local wisdom is effective in improving students’ speaking skills.